Analisis Serapan Hara N, P dan K Jaringan Cabai (Capsicum sp.) pada Variasi Tingkat Kemasaman Tanah - Sangkala, Sangkala; Sunardi, Sunardi; Susilawati, Susilawati (JURNAL AGROTROPIKA, 2024)
This research tested the effect of soil acidity level on the uptake of macro elements in plant tissue. This research is a type of experimental research that examines the effect of soil acidification levels on the absorption of N, P, and K nutrients in chili plant tissues. This research was conducted on the greenhouse experimental land of the Sambas State Polytechnic, Sambas Regency, West Kalimantan. This activity is carried out from March to October 2022. The research design used a descriptive analysize with three treatments, namely pH = 6 (P1), pH = 7 (P2), and pH = 8 (P3) which were repeated as many as 3 tests. Each treatment consisted of 30 plants planted in a planting medium mixed with soil, burnt husks and animal dung. N, P and K uptake is obtained through the analysis of the covering of stem and leaf tissues. The results showed that the difference in the level of acidification of the growing media did not have a effect on the level of absorption of nitrogen and phosphorus, but level of acidification have effect in potassium absorption in chili plants. Nitrogen content generally decreases in plant tissue samples aged 30 to 45 days after planting, while in plants aged 45 to 50 days after planting, there is enerally an increase in the accumulation of nitrogen in plant tissues. Absorption of phosphorus elements in tissues fluctuates over a period of 30 to 60 days after planting. The phosphorus content found in leaf tissue treatment pH 6 and pH 7 increased from the observation period of 30 to 60 days after planting. Absorption of potassium elements in tissues fluctuates over a period of 30 to 60 days after planting. An increase in Potassium content in stem and leaf tissues occurred in pH 6 treatment samples. Key words : chili, nitrogen, phosphor, potassium, uptake